2020
DOI: 10.1108/jeas-02-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Disinvestment in Indian central public sector enterprises: a performance improvement measure

Abstract: PurposeThe purpose of this study is to represent an attempt to empirically capture the impact of disinvestment on the financial and operating performance of 26 Bombay Stock Exchange (BSE) listed central public sector enterprises (CPSEs) in India which got divested through stock market mechanism during the time period of 2000–2014.Design/methodology/approachThrough ratio analysis different ratios such as return on assets, return on equity, net income efficiency, debt equity, dividend payout and employment level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Theoretically, this paper responds to the gaps concerning financial performance analysis of Disinvested Central Public Sector Enterprises in India. Mandiratta and Bhalla (2021) stated that most of the privatization-related studies in Indian context are found to be of conceptual nature and the majority portion is restricted to the examination of traditional accounting measures only. As such, the studies measuring the impact of disinvestment on the financial and operating performance of CPSEs divested through public offering mode are at best scarce or absent.…”
Section: Discussion Contribution and Implications Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, this paper responds to the gaps concerning financial performance analysis of Disinvested Central Public Sector Enterprises in India. Mandiratta and Bhalla (2021) stated that most of the privatization-related studies in Indian context are found to be of conceptual nature and the majority portion is restricted to the examination of traditional accounting measures only. As such, the studies measuring the impact of disinvestment on the financial and operating performance of CPSEs divested through public offering mode are at best scarce or absent.…”
Section: Discussion Contribution and Implications Of The Studymentioning
confidence: 99%
“…Also, one of the well-known facts about privatization policy, as far as its motive is concerned, has been to improve the functioning of sick and loss making public sector units. As such, privatization has proved to be an effective strategy of the government as well as a performance improvement measure (Mandiratta and Bhalla, 2021) similar to benchmarking. Therefore, this study is a great contribution to benchmarking directly in terms of performance measurement through standards and indirectly through the mechanism of privatization.…”
Section: Theoretical Contributions Of the Studymentioning
confidence: 99%